Emission rates of intermodal rail/road and road-only transportation in Europe: A comprehensive simulation study. (December 2018) - Heinold, Arne; Meisel, Frank
Highlights: Greenhouse gas emissions are estimated for intermodal rail/road and road-only routes. Large freight shipments are simulated within and between 27 European countries. We consider traffic conditions, train utilization, payload, power supply, etc. It is shown that emission rates vary strongly among country pairs. Intermodal routing emits less greenhouse gases for over 90% of the shipments. Abstract: Intermodal rail/road transportation combines advantages of both modes of transport and is often seen as an effective approach for reducing the environmental impact of freight transportation. This is because it is often expected that rail transportation emits less greenhouse gases than road transportation. However, the actual emissions of both modes of transport depend on various factors like vehicle type, traction type, fuel emission factors, payload utilization, slope profile or traffic conditions. Still, comprehensive experimental results for estimating emission rates from heavy and voluminous goods in large-scale transportation systems are hardly available so far. This study describes an intermodal rail/road network model that covers the majority of European countries. Using this network model, we estimate emission rates with a mesoscopic model within and between the considered countries by conducting a large-scale simulation of road-only transports and intermodal transports. We show that there are high variations of emission rates for both road-only transportation and intermodal rail/road transportation over the different transport relations in Europe. We found that intermodal routing is more eco-friendly than road-only routing for more than 90% of the simulated shipments. Again, this value varies strongly among country pairs.